Changes in wage distributions of wage earners in Canada: 2000-2005 - Kao-Lee Liaw; Lei Xu (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2013)
This research attempts to figure out whether the wage distributions of Canadian wage earners have been moving towards or away from the flowing three ideals in the early part of the 21th century. First, there be a pattern of wage increase that is shared by a large majority of wage earners. Second, the historical gender inequality in wage be reduced. Third, there be a decrease in wage inequality for both males and females. We use the long-form records of the 2001 and 2006 population censuses to carry out our investigation. A nice feature of these records is that the values of income variables are not top-coded so that the true averages will not be understated and good insights into the situations of those with extremely high incomes can be obtained. We are disappointed by finding that the Canadian economy mostly drifted away from our three ideals, with the main exception being that for female wage earners the improvement in wage was fortunately shared by a large majority. We believe that an important reason for our disappointing finding is the progressive entrenchment of market fundamentalism in Canada. Incidentally, we have discovered that Statistics Canada did a good job in designing the 2006 census questionnaire so that the annoying choppiness that occurred to the 2000 wage distributions vanished in the 2005 wage distributions.
Keywords: D31; H31; H24; 330; male and female wage distributions; gender inequality; wage inequality; Canada; long-form census records; market fundamentalism